Layer-by-Layer Nanoassemblies for Vaccination Purposes - Eduardo Guzmán; Francisco Ortega; Ramón G. Rubio (MDPI AG, 2023)
In recent years, the availability of effective vaccines has become a public health challenge due to the proliferation of different pandemic outbreaks which are a risk for the world population health. Therefore, the manufacturing of new formulations providing a robust immune response against specific diseases is of paramount importance. This can be partially faced by introducing vaccination systems based on nanostructured materials, and in particular, nanoassemblies obtained by the Layer-by-Layer (LbL) method. This has emerged, in recent years, as a very promising alternative for the design and optimization of effective vaccination platforms. In particular, the versatility and modularity of the LbL method provide very powerful tools for fabricating functional materials, opening new avenues on the design of different biomedical tools, including very specific vaccination platforms. Moreover, the possibility to control the shape, size, and chemical composition of the supramolecular nanoassemblies obtained by the LbL method offers new opportunities for manufacturing materials which can be administered following specific routes and present very specific targeting. Thus, it will be possible to increase the patient convenience and the efficacy of the vaccination programs. This review presents a general overview on the state of the art of the fabrication of vaccination platforms based on LbL materials, trying to highlight some important advantages offered by these systems.